Іван Вишенський: проблема символічної біографії - Білоус, Петро; Bilous, Petro (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті з’ясовується проблема символічної біографії на матеріалі поеми «Іван Вишенський» І. Франка. Розглядається специфіка Франкового творення образу І. Вишенського, творча біографія І. Франка, водночас до певної міри розвінчується образ видатного полеміста, вивільнений від Франкових рефлексій і тим самим реалістично представлений як постать на тлі історичної епохи.In the article the problem of symbolic biography using the material of І. Franco’s poem “Ivan Vyshenskyi” is cleared up. The specific of Franko’s creation of I. Vyshenskyi character, І. Franco’s creative biography are being examined, at the same time the character of prominent polemicist, disengaged from Franko’s reflections is dethroned and is realistically presented as a figure at the historical epoch background.
Ivan Vуshensky: Problem of Symbolic Biography
Keywords: І. Франко; І. Вишенський; біографія; аскетизм; свобода вибору; І. Franko; І. Vyshenskyi; biography; asceticism; freedom of choice